Retraction Note to: Ultrasound Elastography supplement assessing nodal status of magnetic resonance imaging staged cervical N0 patients with nasopharyngeal carcinoma - Jian Li; Fei Han; Yunxian Mo; Xindan Chen; Yong Li; Feifei Zuo (Cancer Imaging, 2019)
The Editors have retracted this article [1] because figure 2 has been substantially duplicated from a previously published article by Chen B et al., 2018 [2]. There is also significant and uncited overlap in the patient population between the two articles resulting in concerns relating to the scientific validity and novelty of the data.